(untitled) (International Journal of Innovative Technologies in Economy, 2020)
Since 1978, China’s economy has opened to the world. Over the past 40 years, China’s capital stock has grown at an annual rate of 6.9%. China began to implement the “Going out” policy in 2002, mainly to promote its overseas investment activities. The Chinese government launched a rescue plan of 4 trillion yuan in 2008, hoping to shift from export led growth to promote the expansion of the internal market. In this paper, China imports to Mongolia have increased year by year, accounting for 33.5% of its imports in 2018. China has pledged to invest globally by 1.25 trillion USD in 2025, and has increased investment in Mongolian mineral deposits. When the Chinese economy was in the “New Normal”, it proposed the “Belt and Road” initiative. To strengthen the connection between the “Belt and Road” and the “Steppe Silk Road” initiative, 32 projects will be implement in Mongolia. After reform and opening up, China has made great achievements. But, the upgrading of industrial structure and technological progress are still slow, economic growth continues to slow down, the aging population is becoming more serious, and the production capacity is seriously surplus. From Mongolia, there are abundant natural resources, and the mining industry is driving economic growth. The economic growth rate is relatively fast, but the industrial structure is single, the evolution of the industrial technology system is stagnation, and the human resources are insufficient, resulting in excessive dependence on foreign trade. The economic situation depends on the neighboring countries, the inflation is serious, and the unemployment rate remains high. Therefore, under such circumstances, China and Mongolia should make good use of the geographical advantages of their neighbors, enhance mutual trust, strengthen economic trade cooperation, maintain the unity of their countries and maintain the strategic balance of international power and jointly create political mutual trust and economic cooperation. This paper takes China Mongolian cooperation as the main research line, and explores new ways for economic and trade cooperation to promote the upgrading of industrial structure and sustained economic growth of the two countries. In addition, as the main component of the “Belt and Road” initiative, Mongolia strengthens economic and trade cooperation with China and promotes the improvement of the level of cooperation between the two countries, and can also achieve long term common development.